Contributions to Odontogryllini (Orthoptera: Gryllidae: Landrevinae) with comments on its taxonomic status and description of a new species of Xulavuna de Mello & Campos, 2014 - Oya, Beatriz Harumi Kondo; Santos, Luiz Augusto Padilha; Fernandes, José Antônio Marin; Tavares, Gustavo Costa (Zootaxa, 2024)
Odontogryllini is a tribe of ground-dwelling crickets exclusive to America. After several taxonomic rearrangements, this tribe has five genera and 23 species now placed in the subfamily Landrevinae. These crickets have dorsoventrally depressed bodies and are moderately to densely covered with bristles. The males may bear tegminal, metanotal, or tergal glands. In this contribution, we discuss the taxonomic status and the morphological features of Odontogryllini and the other two tribes of Landrevinae: Landrevini and Prolandrevini. The presence of dorsal spines between the outer spurs of the hind tibia distinguishes Odontogryllini from Prolandrevini, and the straight or slightly arcuate but never S-shaped stridulum from Landrevini. We also propose the enlarged and plate-like rami as a diagnostic characteristic to distinguish Odontogryllini from Landrevini. Additionally, we describe a new species of the genus Xulavuna de Mello & Campos from the Brazilian Amazon Rainforest, named Xulavuna krenakore sp. nov..